Development of Diagnostic Test for Learning Difficulties in Geometry Material on Junior High School Students - Dany, Diendha Chaniesya Achma; Duskri, M. ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Geometry is one of the mathematics topics that often causes difficulties for junior high school students because it requires visual-spatial abilities and a structured understanding of concepts, leading to misconceptions and procedural errors that impact students' low learning achievement. This research aims to develop a diagnostic test to identify learning difficulties in seventh-grade students regarding geometry material. Researchers used the Research and Development method with the Tessmer model. This stage begins with the preliminary stage, which is conducted thru an analysis of materials and curriculum to design the initial 40 test items. At the self-evaluation stage, the questions are reviewed and refined before being validated. The expert review stage involved two validators, and the initial results showed that 35 questions were suitable and 5 needed revision. In the second stage, all questions were declared suitable. One-on-one testing with several students showed the questions were understandable without further revision, while small group testing with 60 students resulted in 18 questions being acceptable, 17 needing revision, and 5 being eliminated. The final results show 11 easy questions, 28 medium questions, and 1 difficult question, with a reliability coefficient of 0.826, which is considered very high. This diagnostic test is able to identify students' difficulties in understanding concepts, procedures, and misconceptions. Thus, the developed instrument is effective in mapping students' learning weaknesses and supporting more targeted lesson planning.